Where Is Kuta? - Kolawole, Olusegun (Macmillan Nigeria Publishers Ltd, 2006)
Poor Kuta has contracted AIDS. Tolu and his friends who are learning and creaing awareness about the disease endeavour to help.Will they be able to save Kuta?
Keywords: AIDS; Juvenile Fiction; Realistic